Development of early mathematical skills with a tablet intervention: a randomized control trial in Malawi - Pitchford, Nicola J. (Frontiers in Psychology, 2015)
Evaluation of educational interventions is necessary prior to wide-scale rollout. Yet very few rigorous studies have been conducted on the effectiveness of tablet-based interventions, especially in the early years and in developing countries. This study reports a randomized control trial to evaluate the effectiveness of a tablet intervention for supporting the development of early mathematical skills in primary school children in Malawi. A total sample of 318 children, spanning Standards 1–3, attending a medium-sized urban primary school, were randomized to one of three groups: maths tablet intervention, non-maths tablet control, and standard face-to-face practice. Children were pre-tested using tablets at the start of the school year on two tests of mathematical knowledge and a range of basic skills related to scholastic progression. Class teachers then delivered the intervention over an 8-weeks period, for the equivalent of 30-min per day. Technical support was provided from the local Voluntary Service Overseas (VSO). Children were then post-tested on the same assessments as given at pre-test. A final sample of 283 children, from Standards 1–3, present at both pre- and post-test, was analyzed to investigate the effectiveness of the maths tablet intervention. Significant effects of the maths tablet intervention over and above standard face-to-face practice or using tablets without the maths software were found in Standards 2 and 3. In Standard 3 the greater learning gains shown by the maths tablet intervention group compared to both of the control groups on the tablet-based assessments transferred to paper and pencil format, illustrating generalization of knowledge gained. Thus, tablet technology can effectively support early years mathematical skills in developing countries if the software is carefully designed to engage the child in the learning process and the content is grounded in a solid well-constructed curriculum appropriate for the child’s developmental stage.
shortDOI: 10/f7chs2 KerkoCite.ItemAlsoKnownAs: 10.3389/fpsyg.2015.00485 10/f7chs2 2129771:JKQZXRI4 2339240:9JLFSKL8 2339240:JBNHVDFI 2339240:T5JKI3Z2 2339240:VHWCDGSL 2339240:XG5MYJGE 2405685:FRZ847WF 2405685:GQ3CW5G9 2405685:ILEWWQGE 2405685:KZAT29AX 2405685:PT9BHI7C 2405685:VDSNMXIP
Keywords: Evaluation; Mathematics; Tablets; Technology; ___working_potential_duplicate; intervention; primary school; randomized control trial

Implementation Completion and Results Report for a Project to Improve Education Quality in Malawi - World Bank (2015)
KerkoCite.ItemAlsoKnownAs: 2339240:K85DTG8S 2405685:FCZDMWUH

Factors determining digital divide in Ghana's basic schools - Quaicoe, James Sunney; Pata, Kai (2015 IST-Africa Conference, 2015)
This paper explores the concept of digital divide (DD) in Ghana’s basic schools in Sekondi-Takoradi Metropolis in Western Region. We tested the ICT culture variables as well as school location factor in respect to school’s digital divide. A survey sample contained 17 regional city schools from three different locations – central city in the region, towns away from the central city, and village schools. The survey instrument was developed with ten ICT culture variables. The variables in the instrument met the Cronbach’s Alpha threshold value of α = 0.70. Data was analysed with Descriptive statistics, Hierarchical Cluster analysis, Independent t-test, and Canonical discriminant analysis. We found that school location did not determine the schools DD, nonetheless the schools were digitally divided, – 2 clusters were found among schools. This DD was determined by certain ICT culture variables: Teacher’s ICT competences and the usage of ICT in Teacher’s professional practice were paramount.
KerkoCite.ItemAlsoKnownAs: 10.1109/istafrica.2015.7190518 10/ggn3wz 2339240:H83HTANQ 2405685:XZBJRR36